Implementation of Digital Media in Learning Indonesian Language in Class IV MI Al Islam Majasem Purbalingga - Prihatin, Metros (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The Indonesian language subject is one of the subjects that is indispensable in the world of education and has a major role in the growth of science, culture, social and the expression of students' feelings. Indonesian is the national language and as a formal language used in all fields. At the elementary school/madrasah Ibtidaiyah level, the competencies that must be mastered by students in this learning include students being able to read, understand reading, both in the form of text, and those presented in non-text form. It is not an easy thing, to do